Explaining Filipino Households' Declining Saving Rate - Akiko Terada-Hagiwara (Asian Development Bank (ADB), 2009)
From 1994 to 2006, the average household saving rate in the Philippines declined by 5.2 percentage points to about a mere 5% of disposable income. Using data from income and expenditure survey at the household level, this paper explains why households' consumption growth had been higher than income growth during this period. Tracing cohorts shows that saving declined across all demographic groups. A simple test that provides the strength of the precautionary saving motive yields a plausible explanation that households are financially constrained and less prudent in the recent years. This paper argues that these patterns are best explained by the extended coverage of social security system during the 1990s in the Philippines. Less prudent behavior may have been amplified by the severe financial constraint leading to the sharp fall in the saving rate.
hdl:11540/4232
Keywords: 330